2018
DOI: 10.1159/000492335
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Tracheobronchial Tuberculosis in Pulmonary Tuberculosis: A Multicentre, Large-Scale and Prospective Study in Southern China

Abstract: Background: Patients with pulmonary tuberculosis (PTB) have a high risk of concomitant tracheobronchial tuberculosis (TBTB), which commonly causes severe complications such as tracheobronchial stenosis. The prevalence and predictors of TBTB in China remain unclear due to the lack of prospective and large-scale studies. Objectives: To investigate the incidence of TBTB in PTB patients in southern China, and elucidate the predictors of TBTB and related tracheobronchial stenosis. Methods: We prospectively performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 22 publications
(25 reference statements)
6
32
0
Order By: Relevance
“…Furthermore, undergoing the bronchoscopic examination is uncomfortable and costly for older individuals and, therefore, certain older patients refused to undergo bronchoscopic examination in the current study. The present results indicated that female patients with TB were more prone to having TBTB than male patients and that sex was an independent risk factor for concomitant TBTB and tracheobronchial stenosis, which is consistent with previous studies (12,13,20). Several possible reasons may explain why female patients were more likely to present with TBTB including the bronchial structure, as well as sociocultural and aesthetic factors (21).…”
Section: Diagnostic Yield (%/Totals) --------------------------------supporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, undergoing the bronchoscopic examination is uncomfortable and costly for older individuals and, therefore, certain older patients refused to undergo bronchoscopic examination in the current study. The present results indicated that female patients with TB were more prone to having TBTB than male patients and that sex was an independent risk factor for concomitant TBTB and tracheobronchial stenosis, which is consistent with previous studies (12,13,20). Several possible reasons may explain why female patients were more likely to present with TBTB including the bronchial structure, as well as sociocultural and aesthetic factors (21).…”
Section: Diagnostic Yield (%/Totals) --------------------------------supporting
confidence: 93%
“…It is interesting to note that no history of smoking was an independent risk factor for concomitant TBTB, which is consistent with the results of Su et al (13); a possible explanation is that smoking may produce changes in the airway epithelium, thereby preventing MTB from growing in the airways (13). Certain studies have indicated that a longer clinical symptom duration may correlate with longer exposure to Myobacterium tuberculosis and contribute to the development of TBTB (12,13). In the present study, the parameter of longer clinical symptom duration was associated with concomitant TBTB, as determined by univariate analysis.…”
Section: Diagnostic Yield (%/Totals) --------------------------------supporting
confidence: 91%
See 1 more Smart Citation
“…Tuberculosis (TB) is a major global health problem associated with significant morbidity and potential mortality (1,2). Diagnostic bronchoscopy studies have suggested that 10-50% of patients with pulmonary TB have tracheobronchial TB (TBTB) (3,4). Airway stenosis is the most common complication of TBTB.…”
Section: Introductionmentioning
confidence: 99%
“…China has a high prevalence of tuberculosis with about 900,000 new cases of tuberculosis every year; about 10-40% of active tuberculosis patients have concomitant TBT [8], and about 23.3% of patients develop severe airway stenosis [9]. Regular bronchoscopy is invasive and may cause pain.…”
Section: Discussionmentioning
confidence: 99%